Impact of Portfolio Authentic Assessment on Students’ Learning Outcomes of Nahwu at Modern Islamic Boarding School - Ihwan Mahmudi; Aisyah Imani; Chevira Yasin Indriyanti; Rohani Pooteh (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2023)
The study aimed to investigate the potential beneficial impact of portfolio assessment on the learning outcomes of Nahwu lessons of fourth-grade students at the Modern Islamic Boarding School of Al-Ikhlash Female in Kuningan, West Java. The study used an experimental methodology and a quantitative research approach. The research sample included all fourth graders. The research was carried out during the odd semester of academic year 2022. A quasi-experimental design used to evaluate the effectiveness of portfolio assessment, with the experimental class implementing portfolio assessment while the control class continued to use the standard evaluation method. The learning outcomes of the students in the control class produced an average score of 71.67. Comparing the experimental class’ score, which used portfolio assessment, it become clear that the students’ comprehension of the Nahwu material had significantly improved. These results showed that portfolio evaluations have a chance to improve fourth-grade students’ learning outcomes in Nahwu.